O brincar de bebês-mães e sua relação com o desenvolvimento psíquico, linguístico e motor - Schmitt, Patricia Menezes (2019)
This dissertation aimed to analyze the evolution of play related to the cognitive, linguistic and motor development in infants between nine and 24 months, with and without psychic risk. The play analysis script was the instrument that guided the analysis of the filming of this research. This instrument evaluated the behaviors of the baby and the mother during play, and contemplated the verification of the cognitive and intersubjective aspects of the baby's play; and on the support and investment in playing on the part of the mother. The script was prepared by the researchers of this study, in the perspective of contemplating cognitive and intersubjective aspects in play. The study sample consisted of 32 full-term children, with 56.2% males and 43.8% females. Of these children, 13 presented psychic risk from the analysis of the IRDI script and seven children by the evaluation of the PREAUT Signals. The mean gestational age was 39 weeks. There was a significant difference in relation to the pleasure of the child in the experience with the object (p = 0.002), as well as the pleasure and maternal commitment in the activity of playing with the child (p = 0.010), with lower number of behaviors in the group with psychic suffering when compared to the group without psychic suffering. With regard to the creative use of the object, it was evident in this group that this category appears, after the group without suffering, around 18 months of age (p = 0.004), demonstrating effects of psychic risk on cognition and language. It can be concluded that there was an significant association between the characteristics of play and psychic suffering. There were descriptive differences regarding language, motor and cognition between the group with and without psychic suffering.